2022
DOI: 10.1038/s41467-022-33156-5
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of microtubule into GTP-responsive nanocapsules

Abstract: Nanocapsules that collapse in response to guanosine triphosphate (GTP) have the potential as drug carriers for efficiently curing diseases caused by cancer and RNA viruses because GTP is present at high levels in such diseased cells and tissues. However, known GTP-responsive carriers also respond to adenosine triphosphate (ATP), which is abundant in normal cells as well. Here, we report the elaborate reconstitution of microtubule into a nanocapsule that selectively responds to GTP. When the tubulin monomer fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…2c, h ). NS GTP/GTP* has a leaf-like 2D structure and a thickness of approximately 5 nm, corresponding to the thickness of the THD units, as confirmed by atomic force microscopy [ 21 ]. Both MT GTP and MT GTP* , which are prepared from THD GTP and THD GTP* , respectively, are formed by the edge-closing of NS GTP and NS GTP* , which act as [ 28 ], and the long axis of THD GTP is known to be shorter than that of THD GTP* [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2c, h ). NS GTP/GTP* has a leaf-like 2D structure and a thickness of approximately 5 nm, corresponding to the thickness of the THD units, as confirmed by atomic force microscopy [ 21 ]. Both MT GTP and MT GTP* , which are prepared from THD GTP and THD GTP* , respectively, are formed by the edge-closing of NS GTP and NS GTP* , which act as [ 28 ], and the long axis of THD GTP is known to be shorter than that of THD GTP* [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…2d ) containing multiple guanidinium ion (Gu + ) and benzophenone (BP) groups. Glue CO2– molecules can strongly attach to proteins under physiological conditions through the formation of multivalent salt bridges between Gu + ions and oxyanionic functional groups followed by photocrosslinking via BP units [ 21 ]. Molecular dynamics simulations have suggested that the adhesion of Glue CO2– transforms NS GTP/GTP* into a planar structure, resulting in the stacking and assembly of NS GTP/GTP* to construct spherical NC GTP/GTP* .…”
Section: Resultsmentioning
confidence: 99%
“…Nanocapsules serve as excellent drug carriers for sustainedrelease due to their special core-shell structure for the encapsulation and release of active substances. [24][25][26][27][28][29] There are several criteria for the design of smart nanocapsules, including their accurate core-shell structure, smart responsiveness and biocompatibility. [30][31][32][33][34][35] Polyzwitterions contain an equal oppositely charged group in a single repeated unit and are well-known for their excellent hydration, biocompatibility and thermal response (a typical UCST polymer), making them an ideal candidate for constructing biomedical nanocapsules.…”
Section: Introductionmentioning
confidence: 99%
“…And, in most cases, it means that a single engineering-intensive design on proteins results in only one unchangeable assembly, , which is different from natural protein assemblies with transformable or dynamic properties through the formation of diverse noncovalent interactions between proteins. As such, an approach that can readily assemble protein into various architectures with precise protein arrangement by directing the formation of noncovalent interactions between proteins rather than redesigning or replacing specific PPI is highly valuable. There have been some efforts on modulation of PPI by using synthetic ligands, especially the dendritic molecular glues, which is successful in controlling the aggregation and activity of biomacromolecules. But it is hard to employ such ligands in the design of precise protein arrays due to their imprecise artificial binding to proteins, especially the uncontrollable location and number of binding sites. …”
Section: Introductionmentioning
confidence: 99%
“…There have been some efforts on modulation of PPI by using synthetic ligands, especially the dendritic molecular glues, which is successful in controlling the aggregation and activity of biomacromolecules. But it is hard to employ such ligands in the design of precise protein arrays due to their imprecise artificial binding to proteins, especially the uncontrollable location and number of binding sites. …”
Section: Introductionmentioning
confidence: 99%